RESOURCE SAVING AT FERROUS METALLURGY ENTERPRISES - Xashimova Salima Nigmatullayevna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article describes the key areas for rational use of material resources and resource conservation. It is enlightened the example of the APO "Uzmetkombinat".